Case study of a world hour record simulation in an elite cyclist: Insight into task failure - Kordi, M.; Bigham, D.; Tipper, J.; Ferguson, R. A.; Howatson, G.; Wale, J. (European Journal of Sport Science, 2024)
The `cycling hour-record` is one of the most prestigious events in cycling. However, little detailed analysis of such attempts is available. In preparation for a successful cycling hour-record attempt, an elite cyclist performed a full-hour simulation to provide insights into performance, physiological, aerodynamic and biomechanical limitations that could be identified in the preparation for a subsequent official attempt. Performance (speed, lap time, power and cadence), physiological (heart rate and estimated body temperature), aerodynamic (CDA, helmet angle, rotation and rock) and biomechanical (helmet, thigh and foot position changes) measurements were made throughout the attempt, in which an even-pacing strategy was employed where the point of task failure was defined as the lap which the rider could no longer perform at the targeted lap split (16.6 s) or quicker. The cyclist did not achieve the target distance (54,000 m) during the simulation. The final distance achieved for the hour was 53,250 m. Task failure occurred at 38 min and 33 s (lap 139/34,750 m) into the simulation. Notably, there was a decrease in power output, accompanied with an increase in the estimated body temperature, changes in pedalling kinematics and an increase in aerodynamic drag. The reduction in performance (leading to task failure) during a cycling hour record simulation is underpinned by a decrease in power output as well as an increase in aerodynamic drag due to biomechanical changes in the cycling technique.